Effect of Mango Peel and Pulp Extract on the Quality Characteristics of Chicken Nuggets - Kadakadiyavar, P.; Ambadkar, R. K.; Rathod, K. S. (Journal of Meat Science, 2016)
In the present study the effects of mango peel extract (MPeE), mango pulp extract (MPuE) and butylated hydroxyanisole (BHA) on the keeping quality of chicken nuggets was assessed. The results indicated significantly lower (p<0.05) pH, TBARS and peroxide value (PV) of the products containing 0.5% MPeE. Moisture and fat decreased (p<0.05) significantly during the storage (4±10C) period of 25 days. Total plate count and pyschrophillic count for the products containing 0.5% MPeE and MPuE were significantly (p<0.05) low as compared to control and BHA. Significantly (p<0.05) higher scores for various attributes were observed for the products containing 0.5% MPeE. There was significant (p<0.05) decline in all the sensory attributes of all the products during storage period. It was concluded that MPeE added at 0.5% level found to be an efficient alternative over BHA in processed meats.